Crohn's & colitis 360 (Oxford University Press, 2019)
A peer-reviewed, online-only, open access journal. Publishes engaging and informative content that catalyzes dialogue on state-of-the-art comprehensive care for patients with inflammatory bowel disease (IBD) alongside the latest research to advance prevention, treatment and cures. The journal provides a forum for the dissemination of novel insights and innovations across key disciplines involved in IBD care.
Keywords: Crohnova nemoc; gastroenterologie; syndrom dráždivého tračníku; Crohn Disease; Irritable Bowel Syndrome; kolitida; Colitis